2023
DOI: 10.4012/dmj.2022-093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thickness on the translucency of resin-based composites and glass-ceramics

Abstract: This study was aimed to evaluate the effect of thickness (1, 2, 3, and 4 mm) on the translucency of resin-based composites (RBCs) and glass-ceramics, and compare the influence of the thickness of those materials on the translucency parameter (TP) value. The materials were divided into two groups, eight RBCs in Group 1 and five glass-ceramics in Group 2 and TP, ΔL*, Δa*, and Δb* were compared. Statistically significant differences were present in the 2, 3, and 4 mm in the TP, in the 2 and 4 mm in ΔL*, and in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
3
3
0
Order By: Relevance
“…The findings of this study demonstrated that translucency and opalescence varied with different thicknesses. TP 00 exhibited a continuous decline and curvilinear relationship with increasing thickness, consistent with previous studies [ 8 , 14 , 15 , 38 , 39 ]. While, the variations in opalescence (OP) were material-dependent, indicating differences among the materials.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The findings of this study demonstrated that translucency and opalescence varied with different thicknesses. TP 00 exhibited a continuous decline and curvilinear relationship with increasing thickness, consistent with previous studies [ 8 , 14 , 15 , 38 , 39 ]. While, the variations in opalescence (OP) were material-dependent, indicating differences among the materials.…”
Section: Discussionsupporting
confidence: 91%
“…We observed the highest average variations in TP 00 (TP 00 = 9.72) between 0.5mm and 1.0mm and the lowest (TP 00 = 3.41) between 1.5mm and 2.0mm, aligning with findings by Bayindir et al [ 38 ]. Similarly, Kang et al found that TP decreased as the thickness of resin-based composites and glass–ceramics increased, particularly at lower thicknesses [ 14 ]. However, this observation may be attributed to the limitations of clinical spectrophotometer, as variations in accuracy have been reported between clinical spectrophotometer like Vita Easyshade V and laboratory spectrophotometer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ndings of this study demonstrate a signi cant decrease in irradiance with increased RBC specimen thickness across all shades except between 3 and 4 mm A3D shade specimens, which is consistent with the results of a previous study [12]. This observation led to the rejection of the rst null hypothesis.…”
Section: Discussionsupporting
confidence: 91%